2019
DOI: 10.1038/s41390-019-0634-y
|View full text |Cite
|
Sign up to set email alerts
|

Predicting intestinal recovery after necrotizing enterocolitis in preterm infants

Abstract: BACKGROUND: Intestinal recovery after NEC is difficult to predict in individuals. We evaluated whether several biomarkers predict intestinal recovery after NEC in preterm infants. METHODS: We measured intestinal tissue oxygen saturation (r int SO 2 ) and collected urinary intestinal-fatty acid binding protein (I-FABP u ) levels 0-24 h and 24-48 h after NEC onset, and before and after the first re-feed. We assessed intestinal recovery in two ways: time to full enteral feeding (FEFt; below or equal/above group's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…This suggests that intestinal recovery, including recovery of enterocyte function, is different after surgical intervention than during conservative treatment, possibly due to the removal of affected tissue. Similarly, in the NaNECtrial we previously found that intestinal oxygen saturation measurements after the first enteral re-feed after NEC was associated with FEFt, particularly in the conservatively treated group, while not in the surgically treated group [18] .…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…This suggests that intestinal recovery, including recovery of enterocyte function, is different after surgical intervention than during conservative treatment, possibly due to the removal of affected tissue. Similarly, in the NaNECtrial we previously found that intestinal oxygen saturation measurements after the first enteral re-feed after NEC was associated with FEFt, particularly in the conservatively treated group, while not in the surgically treated group [18] .…”
Section: Discussionsupporting
confidence: 55%
“…First, the NoNEC trial (NTR3239) was performed between 2010 and 2012 [17] . Second, the NaNEC trial (NTR4816) was performed between 2015 and 2017 [18] . In both trials, the onset of NEC was defined as the time of the first abdominal X-ray made upon clinical suspicion of NEC including X-rays performed in referring hospitals.…”
Section: Methodsmentioning
confidence: 99%
“…Some of the foci of management strategies at our center include careful postoperative fluid and nutritional management, early and aggressive enteral feeding advancement, and use of PN to achieve goal macronutrient provision [25]. There is emerging literature on biomarkers to predict intestinal recovery [26]. Novel treatments such as teduglutide, a recombinant human glucagon-like peptide-2 analog that promotes an intestinal adaptive response, may be the next strategy to achieve enteral autonomy in these patients [27].…”
Section: Discussionmentioning
confidence: 99%
“…In a 2019 prospective observational cohort study, Kuik, et al measured the regional intestinal oxygen saturation (r int SO 2 ) by near-infrared spectroscopy (NIRS) and intestinal fatty acid binding protein (I-FABP u ) in the urine of 27 preterm infants. The study found that when measured after the first re-feed, these markers were predictive of post-NEC stricture, though not of recurrent NEC [36]. Additionally, a recent study on infants between 24-40 weeks postmenstrual age found high intestinal alkaline phosphatase (IAP) in stool and low IAP enzyme activity in patients with NEC compared to those without disease; IAP also was a useful biomarker for disease severity [37].…”
Section: Npo Durationmentioning
confidence: 96%